Akshi Tarpana: An Eye Rejuvenation - Sushmita; Anjali (International Research Journal of Ayurveda & Yoga, 2022)
Akshi is the most important Gyan Indriya. It is the site of Alochaka Pitta. Sushruta The Father of Surgery has recommended “Kriyakalpa” for the management of Akshi Roga. The term Kriyakalpa refers to the treatment, which can be applied for almost all types of Akshi Roga. Kriyakalpa comprises of Tarpana, Putpaka, Seka, Aschyotana and Anjana. Akshi Tarpana is a procedure to ensure that the healthy status of the eye is maintained in a normal condition as well as diseased states. In this procedure medicated oil or ghee is retained in the eyes for fixed time in a specific formed frame. According to modern pharmacology, drug penetration depends upon permeability of layers. The epithelium & endothelium of cornea is highly permeable for lipid content, while stroma is permeable to only water content. Thus, fat soluble and water-soluble drugs readily penetrate these layers. In this article there is a review on Akshi Tarpana Karma, their indications, contraindications and possible mode of action is discussed.